2003
DOI: 10.1093/humrep/deg139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intra-uterine cytokine concentration and matrix-metalloproteinase activity in women with recurrent failed embryo transfer

Abstract: In IVF patients with recurrent implantation failure, an altered pattern of intra-uterine cytokine concentration and MMP activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 57 publications
6
62
0
3
Order By: Relevance
“…The immune system plays a role in the aetiology of infertility and in successful implantation (Simon et al, 1998;Sanchez-Cuenca et al, 1999;Ng et al, 2002;Inagaki et al, 2003;Kwak-Kim et al, 2003;Ledee-Bataille et al, 2004a;Ledee-Bataille et al, 2004b;Boomsma et al, 2009). T helper (Th) cells regulate and deviate immune responses through cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…The immune system plays a role in the aetiology of infertility and in successful implantation (Simon et al, 1998;Sanchez-Cuenca et al, 1999;Ng et al, 2002;Inagaki et al, 2003;Kwak-Kim et al, 2003;Ledee-Bataille et al, 2004a;Ledee-Bataille et al, 2004b;Boomsma et al, 2009). T helper (Th) cells regulate and deviate immune responses through cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…The literature contains data on the role of cytokines, free radicals in regulating the activity of metalloproteinases. A separate work on the role of magnesium in the modulation of gelatinase B activity [1,10,11].…”
Section: Abstract: сHronic Endometritis Gelatinase Magnesiummentioning
confidence: 99%
“…Polette et al (13) also observed that MMP-9 was secreted at the highest levels in early pregnancy. Successful embryo implantation requires a suitable intrauterine environment and receptivity; as it has been found that the MMP-9 activities in the endometria of women with failed early pregnancy are significantly increased and result in disorders of ECM components, this suggests that MMP-9 is significant in the failure of pregnancy (14). The present study also detected MMP-9 in the chorionic villi of women in the early stages of pregnancy, suggesting that MMP-9 plays an important role in cytotrophoblast invasion.…”
Section: +mentioning
confidence: 99%